Surgical Clinic of the Hospital Santa Ana - Mimbela, Pablo (1922)
Inaugural lecture of the course of 1922, Surgical Clinic of the Hospital Santa Ana by Professor Dr. Paul Mimbela, Professor at the Faculty of Medicine of the Peruvian Society of Surgery.